Bis-phenanthridinium–adenine conjugates as fluorescent and CD reporters for fine structural differences in ds-DNA/RNA and ss-RNA structures. Issue 3 (2nd April 2016) - Tumir, Lidija-Marija; Šupljika, Filip; Piantanida, Ivo
Abstract: Two structurally similar bis-phenanthridinium–adenine conjugates (equipped with one or two adenines, respectively), exhibiting strong ds-DNA/RNA groove binding, revealed ratiometric fluorescent recognition of alternating AT-DNA with respect to other ds-DNA/RNA and ss-RNA. Further, CD spectra pattern of adenine–bis-phenanthridinium conjugate/polynucleotide complexes strongly depended on polynucleotide secondary structure. Attached adenine was essential for spectrophotometric recognition response, ds-DNA stabilisation and orientation of compounds regarding chiral DNA helix. Abstract :